The Role of Technology in Enhancing Learning Experiences: From Early Childhood Education to Adult Education - Galtimari, Rukaiya Gaji; Biu, Hadiza Aliyu; Ladan , Babangida (Journal of Early Childhood Development and Education, 2025)
Background of study: Technology has become an essential element in modern education. Its rapid development has changed the way students learn and teachers teach at all levels of education. As the need for more flexible, personalized and accessible learning increases, it is important to understand how technology supports learning experiences and what challenges arise from its integration. Aims and scope of paper: This paper aims to explore the role of technology in enhancing learning experiences at different levels of education. The main focus is on identifying the benefits, the impact on cognitive and emotional development, and the challenges and future potential of educational technology. Methods: This study used a qualitative approach through a literature review. Data sources included academic journals, educational reports and relevant case studies. It was analyzed to obtain a comprehensive picture of the application of technology in the learning context. Result: Interactive technology has been shown to have a positive impact on early childhood cognitive and emotional development. At the primary and secondary levels, approaches such as blended learning, game-based learning and adaptive systems increase student engagement and personalization. In higher education, advanced technologies such as AI, AR and VR shape innovative and collaborative learning environments. In adult education, technology supports flexible, skills-based learning through digital platforms and corporate training. Conclusion: Technology has transformed the education process at all levels by improving engagement, accessibility and learning outcomes. However, to fully realize the potential of technology requires continued development, inclusive education policies, and attention to ethics and equity in digital access globally.